Cultural content in English textbook: Analyzing the representation of culture in the English textbook “English for change” - Hakim, Andrean Naufal Maula; Wahyuni, Dewi Sri (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The present study examines the representation of cultural content in cultural representation, English the 11th-grade English textbook “Bahasa Inggris: English for Change.” This descriptive qualitative research employs document analysis as the data collection technique. The study investigates the cultural representation in this Senior High School English textbook using Cortazzi and Jin’s (1999) cultural dimensions and Yuen’s (2011) cultural elements as the analytical framework. The analysis reveals that Indonesian culture is predominantly featured across all textbook units, resulting in a limited representation of foreign cultural dimensions. Practice elements are the most prevalent, followed by product, person, and perspective elements in terms of cultural distribution. The findings indicate an imbalanced representation between Indonesian and foreign cultures, as well as an uneven distribution of the cultural aspects outlined by Yuen's framework (2011). It is recommended that the textbook authors incorporate a more diverse range of cultures to enhance students’ intercultural knowledge.